2022
DOI: 10.3390/electronics11071085
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Resonant Converter Polynomial Model Implemented in a Digital Signal Controller

Abstract: Due to their exceptional performance in coping with large variations in output voltage and current, parallel resonant converters (PRC) are commonly used in high-voltage applications. The incorporation of step-up transformer parasitic components as part of a power topology, on the right duty and a suitable switching frequency, determines the high efficiency and wide variety of applications with PRC. Switching losses are reduced in the same topology by tracking and running on the optimum mode for each power and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…For this purpose, high-frequency transformer-based converters are most commonly used. A literature review performed in the area of high-voltage power supplies for rapid capacitor charging showed that in most cases, topologies with full-bridge converters are used [12][13][14][15][16][17][18][19] due to the versatility of this topology and the possibility of implementing various control algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, high-frequency transformer-based converters are most commonly used. A literature review performed in the area of high-voltage power supplies for rapid capacitor charging showed that in most cases, topologies with full-bridge converters are used [12][13][14][15][16][17][18][19] due to the versatility of this topology and the possibility of implementing various control algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a method with phase-shifted modulation is much more often used [15,16]. In a large number of applications, a resonant converter can be found [17,18]. This method has several benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation